Venom induces alarm behaviour in the social wasp Polybioides raphigastra (Hymenoptera : Vespidae): an investigation of alarm behaviour, venom volatiles and sting autotomy - Hashim, Rosli; Turillazzi, S.; Sledge, M.F.; Dani, F.R.; Fortunato, A.; Maschwitz, U.; Clarke, S.R.; Francescato, E.; Jones, G.R.; Morgan, E.D. (1999)
Chemicals from the venom gland elicited alarm behaviour and attack in the Asian polistine wasp Polybioides raphigastra. When presented with crushed venom glands workers of this wasp respond with a mass stinging attack. Gas chromatography-mass spectrometry analyses show that the major volatiles in the venom gland are alkanes, monounsaturated alkenes and 2-alcohols. Several pyrazines, a spiroacetal and aromatics were also identified as trace compounds. The anatomy and morphology of the sting apparatus are reported, and we describe sting autotomy in this wasp. This is the first such report for the Ropalidiinae. The structures responsible for autotomy are likely to be large barbs present on the sting lancets, and a conspicuous tooth present on the medial side of the left lancet. Sting autotomy in P. raphigastra probably plays an important role in the localization of sites of attack by wasps defending the nest.